2011
DOI: 10.3382/ps.2011-01502
|View full text |Cite
|
Sign up to set email alerts
|

Single or combined effects of mannan-oligosaccharides and probiotic supplements on the total oxidants, total antioxidants, enzymatic antioxidants, liver enzymes, and serum trace minerals in cyclic heat-stressed broilers

Abstract: This study was intended to explore the oxidative status of broilers under cyclic heat stress (HS) as modulated by supplementation of mannan-oligosaccharides (MOS) and a probiotic mixture (PM). Two hundred fifty 1-d-old chicks were randomly divided into 5 groups. From d 22, birds were either kept in a thermoneutral zone (TN; 26.7°C for 24 h/d) or subjected to HS (35 ± 1.1°C and 75 ± 5% RH for 8 h/d from 1000 to 1800 h) to the conclusion of the study on d 42. Birds were fed either a corn-based diet (TN and HS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
45
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 34 publications
13
45
2
Order By: Relevance
“…As a natural protective response against oxidative stress (Sohail et al, 2011;Akbarian et al, 2016), serum total antioxidants have been reported to be increased in HS birds (Sohail et al, 2011). Conversely, HS did not significantly increase the serum antioxidant activity of broilers in the present study.…”
Section: Discussioncontrasting
confidence: 41%
“…As a natural protective response against oxidative stress (Sohail et al, 2011;Akbarian et al, 2016), serum total antioxidants have been reported to be increased in HS birds (Sohail et al, 2011). Conversely, HS did not significantly increase the serum antioxidant activity of broilers in the present study.…”
Section: Discussioncontrasting
confidence: 41%
“…In contrast to our study, Sohail et al (2011) reported that the addition of probiotics mixture decreased serum PON1 concentration in heat-stressed broilers compared to control (thermo-neutral temperature). The difference could be attributed to the experimental condition, probiotics species, dose and duration of the experiment.…”
Section: Discussioncontrasting
confidence: 52%
“…Cp has a variety of functions. It is essential for Fe homeostasis, Cu transportation, and acts as an antioxidant substance (Sohail et al 2011). In serum, Cp level is positively correlated with thiobarbituric acid reactive substances (TBARS) and negatively correlated with vitamin C (Jacobs et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In grower period, the broilers were sensitive to high temperature and humidity, thus broilers need comfortable temperature for optimum production. Comfortable temperature for optimal production in broiler chickens is 18-27 0 C (Kuczynski, 2002;Olanrewaju et al, 2010;Sohail et al, 2011;Aljuobori et al, 2016).…”
Section: Resultsmentioning
confidence: 99%